Integrating Madurese Cultural and Religious–Sociological Perspectives into PGSD Discussions: A Giroux Critical Pedagogy Approach - Iwan Kuswandi; Asmoni; M. Ridwan; Muhammad Hamka; Nurulshahidah binti Hamdan (MIMBAR PGSD Undiksha, 2026)
Local cultural wisdom has the potential to serve as a contextual learning resource for developing twenty-first-century competencies in higher education. However, its limited use has hindered the strengthening of cultural awareness and lecturers’ transformational competencies. This study aims to analyze the integration of Madurese cultural values into academic discussions and its contribution to culturally responsive learning and lecturers’ transformational competencies. A quantitative descriptive approach involving 45 lecturers was employed. Data were collected through a five-point Likert-scale questionnaire and documentation, then analyzed using means and standard deviations. The results showed that most dimensions of cultural integration were rated high, particularly theory contextualization, transformational project development, and the use of local culture-based media and learning resources. However, critical socio-cultural-religious analysis and critical dialogue were rated moderately high, indicating the need to strengthen reflective practices. The study concludes that integrating Madurese cultural values into academic discussions can strengthen culturally responsive learning and lecturers’ transformational competencies. These findings confirm that local wisdom can underpin contextual and reflective higher education oriented toward cultural identity and educational transformation.